Post-traumatic hydrocephalus in a dog - Lopes, C. E. B.; Viana, D. A.; Matos, M. G.; Rodrigues, F. R. N.; Pimentel, S. P. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Hydrocephalus is a condition when an exacerbated amount of cerebral spinal fluid (CSF), occurring due to an abnormally high production, poor drainage or obstructions in the normal flow, is accumulated in the head, generally occasioning an initial dilation of the lateral ventricles, and culminating in many neurological signs, depending on its cause and severity. Additionally, it could be also associated with head traumas, and in these cases, the forensic necropsy is a necessary tool to elucidate all circumstances involved, establishing a perfect correlation between legal and medical aspects especially when there is doubt of a possible crime. The present paper is a case report of a traumatic injury leading to a hydrocephalus condition.